Developing Character-based English Teaching Materials for Elementary School Students through Total Physical Response (TPR) - Rindilla Antika; Elsy Melia Sari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to develop an English teaching material using the Total Physical Response (TPR) learning model and oriented to character education. The Research and Development (RnD) is employed in this study which referred to the Plomp model of development which consisted of four stages. The data were collected through questionnaires, interviews, observation, validity tests, and effectiveness. Subjects of the research were fifth-grade students of SDIT Mutiara Pariaman City and English teachers. Data analyzed were carried out quantitatively and qualitatively. The data were analyzed quantitatively and qualitatively. The validity test showed that the developed product can be employed in the classroom by expert judgments with an average score of 86%. The result in implementing the product showed the product is effectively improving students’ English ability and their ethical values in the learning process. Thus, the English teaching material using the Total Physical Response (TPR) learning model and oriented into character education is feasible and effective to be used in the fifth grade of elementary school.